Econometrics Analysis of Contributions of Primary, Secondary, and Tertiary Sectors in GDP of Nepal - Ramesh Budha, (Journal of Nepalese Management and Research, 2024)
GDP is an essential indicator of a country's economic health, impacted by variables such as inflation, foreign investment, market openness, supply and demand, population, and political environment. The primary sector, which generates raw materials for industries such as agriculture, mining, and quarrying, gives input to the secondary and tertiary sectors. The study's goal is to look into how the primary, secondary, and tertiary sectors influence economic growth.The study looks at the relationship between Nepal's GDP, primary, secondary, and tertiary sectors from 2060/61 to 2078/79. Data were obtained from the NRB, the World Bank, and the Ministry of Finance. Analytic and descriptive approaches were used, using mean and standard deviation for descriptive research and the OLS method for analytical research. E-Views software was utilized for the analysis. The study investigates the elements that influence Nepal's GDP growth, revealing a substantial positive relationship between GDP growth and developments in the industrial, service, and agricultural sectors. The service sector, followed by agriculture and industry, makes a significant contribution. Nepal's small landlocked size and reliance on China and India make it challenging to achieve GDP development. Modernizing agriculture, lowering food imports, and expanding the industrial sector are critical.